Oligo-recurrence predicts favorable prognosis of brain-only oligometastases in patients with non-small cell lung cancer treated with stereotactic radiosurgery or stereotactic radiotherapy: a multi-institutional study of 61 subjects. Issue 1 (December 2016) - Niibe, Yuzuru; Nishimura, Tetsuo; Inoue, Tetsuya; Karasawa, Katsuyuki; Shioyama, Yoshiyuki; Jingu, Keiichi; Shirato, Hiroki
Abstract Background To investigate the prognostic value of oligo-recurrence in patients with brain-only oligometastases of non-small cell lung cancer (NSCLC) treated with stereotactic radiosurgery (SRS) or stereotactic radiotherapy (SRT). Methods Patients treated with SRS or SRT for brain-only NSCLC oligometastases in 6 high-volume institutions in Japan between 1996 and 2008 were reviewed. Eligible patients met 1), 2), and 4) or 1), 3), and 4) of the following: 1) NSCLC with 1 to 4 brain metastases on magnetic resonance imaging (MRI) treated with SRS or SRT; 2) control of the primary lesions (thorax) at the time of SRS or SRT for brain metastases (patients meeting this criterion formed the oligo-recurrence group); 3) with SRS or SRT for brain metastases, concomitant treatment for active primary lesions (thorax) with curative surgery or curative stereotactic body radiotherapy (SBRT), or curative chemoradiotherapy (sync-oligometastases group); and 4) Karnofsky performance status (KPS) ≥70. Results The median overall survival (OS) of all 61 patients was 26 months (95 % CI: 17.5–34.5 months). The 2-year and 5-year overall survival rates were 60.7 and 15.7 %, respectively. Stratified by oligostatus, the sync-oligometastases group achieved a median OS of 18 months (95 % CI: 14.8–21.1 months) and a 5-year OS of 0 %, while the oligo-recurrence group achieved a median OS of 41 months (95 % CI: 27.8–54.2 months) and a 5-year OS of 18.6 %. On multivariate analysis, oligo-recurrence was the only significant independent factor related to a favorable prognosis (hazard ratio: 0.253 (95 % CI: 0.082–0.043) (p  = 0.025). Conclusions The presence of oligo-recurrence can predict a favorable prognosis of brain-only oligometastases in patients with NSCLC treated with SRS or SRT.